Development and performance evaluation of a mechanical pomelo fruit juice extractor - Buang, Nur Salihah (2016)
The aim of the beverage industries in the juice extraction process is to produce juice with high yield while preserving its nutritive values and quality. The pomelo (Citrus grandis (L). Osbeck) fruit flesh compounded with numerous sacs containing juice, which the texture cell wall of juice sacs much more firm compared to other citrus’ fruit sacs. Extraction is one of the most important processes in the fruit juice processing to extract almost all juice from the fruits. Generally, fruit juices are extracted using conventional juice extractor, but there might be some cases where the juice is not optimally extracted, thus yielding a portion of the remaining juice in the pulp. This study aims to develop a juice extractor which able to produce a high juice yield, high extraction efficiency with low extraction loss while preserving the juice quality attributes. Some properties of pomelo fruits were evaluated; namely the physical, chemical and mechanical properties. The development of juice extractor started with the design considerations, and then the several conceptual designs were generated. The details of design process in terms of calculations, selection of suitable materials and the assembly parts for fabrication were discussed in this study. A juice extractor was designed and constructed as an improvement of conventional juice extractor to extract almost juice-free fruit flesh of pomelo sacs. It consists of hopper to feed the fruit flesh, and two main process chamber which crushes and filters chamber. A crushing chamber was provided with a pair of two-level roller-cog to crush the fruit flesh. Then, the filtering chamber provides centrifugal force to spin the crushed fruits from crushing chamber in order to separate juice from pulp and expel more juice to flow out. The results showed that the roller speed of crushing chamber at 1125 rpm and spinning time of 420 s gave the high juice yield (80.07%) and extraction efficiency (81.35%) with lower moisture of pulp waste at 52.31%. The quality attributes based on ascorbic acid, lightness and total soluble solids were not significantly different between the tested roller speed and spinning time. The optimum condition from the developed juicem extractor was then been used for the comparison to the other juice extraction method. The developed juice extractor was compared with the performance of centrifugal juice extractor, screw press type extractor, blending type extractor and hand press. The data obtained indicated that the developed juice extractor yielding high juice yield, high extraction efficiency, low extraction loss and high extraction capacity. Significant differences at p<0.05 were detected in total soluble solids (TSS), titratable acidity, lightness and ascorbic acid but no significant difference between the pH values. Therefore this project is expected to introduce a new knowledge of extraction method to small scale juice processors and may be useful for postharvest technologist, food technologist and food manufacturers